2023
DOI: 10.1007/s00405-023-08139-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and post-operative complications in patients undergoing surgery for advanced pharyngeal or laryngeal cancer

Abstract: Purpose Malnutrition is an important prognostic indicator of post-operative outcomes in patients undergoing surgery for head and neck cancer, however, limited studies utilize validated nutrition assessment tools to accurately assess risk. The aim of this study was to determine the relationship between nutritional status on post-operative complications and length of stay for patients undergoing either a laryngectomy, pharyngectomy or pharyngolaryngectomy for head and neck cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In a study of 637 patients, Zhang et al showed that up to 43.7% of patients could be identified as being at a high risk of malnutrition [38]. Furthermore, the presence of malnutrition is associated with a higher proportion of postoperative complications (81% vs. 42%, p = 0.013) in adults undergoing pharyngectomy or laryngectomy procedures [39]. In a meta-analysis of 22 studies (n = 9332), the risk of malnutrition ranged from 12.8% to 80.8%.…”
Section: What Is the Rationale Of Prehabilitation In Cancer Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 637 patients, Zhang et al showed that up to 43.7% of patients could be identified as being at a high risk of malnutrition [38]. Furthermore, the presence of malnutrition is associated with a higher proportion of postoperative complications (81% vs. 42%, p = 0.013) in adults undergoing pharyngectomy or laryngectomy procedures [39]. In a meta-analysis of 22 studies (n = 9332), the risk of malnutrition ranged from 12.8% to 80.8%.…”
Section: What Is the Rationale Of Prehabilitation In Cancer Patients?mentioning
confidence: 99%
“…Studies on nutritional prehabilitation have used a variety of measurements to assess baseline nutritional status and identify cancer patients who are most at-risk of malnutrition. These incorporate objective nutrition parameters (anthropometric, biochemical, and immunological), subjective measurements (weight change and dietary intake change), and physical assessments (loss of muscle and fat mass) [39,[44][45][46]. It is important to note that, although they are separate conditions, sarcopenia and malnutrition often coexist [42].…”
Section: What Is the Rationale Of Prehabilitation In Cancer Patients?mentioning
confidence: 99%